Accumulated unhealthy behaviours and insomnia in Japanese dwellers with and without cardiovascular risk factors: a cross-sectional study. Issue 4 (15th April 2022) - Kato, Suzuka; Harada, Sei; Iida, Miho; Kuwabara, Kazuyo; Sugiyama, Daisuke; Takeuchi, Ayano; Sata, Mizuki; Matsumoto, Minako; Kurihara, Ayako; Hirata, Aya; Okamura, Tomonori; Takebayashi, Toru
Abstract : Objectives: To date, the association between accumulated unhealthy behaviours and insomnia in individuals stratified according to the presence or absence of major cardiovascular risk factors is unclear. This study aimed to examine the effect of accumulated unhealthy behaviours on insomnia in Japanese dwellers. Design: Cross-sectional study. Setting: Baseline data between April 2012 and March 2015. Participants: Our study used cross-sectional data among Japanese aged 35–74 years in a rural community (N=9565), the attendees of annual municipal or work site health check-up programmes. Main outcome measures: Insomnia was assessed by Athens Insomnia Scale, which was set at 6 points and greater; other scales were given. Participants were categorised into three groups by their number of unhealthy behaviours (no exercise habit, smoking, alcohol drinking, skipping breakfast and obesity): 0–1, 2–3, 4 or more. The association between accumulated unhealthy behaviours and insomnia was estimated by logistic regression analysis. Further analysis was done after stratification of cardiovascular risk factors assessed by anthropometrics and clinical biochemistry measurements. Results: The overall prevalence of insomnia was 13.3% for men and 19.3% for women. Men with unhealthy behaviour factors were more likely to have insomnia after adjusting for potential confounders, compared with the least unhealthy group (trend p=0.013). Women with four or more unhealthy behaviour factors were more likely to have insomnia, compared with the lowest groups (OR 1.175, 95% CI 1.077 to 1.282). Insomnia has an association with the unhealthy behaviours among men without cardiovascular risk factors (lowest groups: OR 1.133, 95% CI 1.037 to 1.238, trend p=0.026). Women without hypertension were more likely to have suspected insomnia, compared with the lowest group (OR 1.215, 95% CI 1.101 to 1.341). Conclusion: The results showed accumulated unhealthy behaviours were associated with increased risk of insomnia in Japanese dwellers. For healthy population without cardiovascular risk factors, unhealthy behaviours should be considered as background conditions for insomnia.